PEMBATALAN PERKAWINAN AKIBAT WALI NIKAH TIDAK SAH - Saarah Faadhilah; Setyaningsih Setyaningsih (Reformasi Hukum Trisakti, 2021)
Humans usually have the desire to have a life partner and offspring, one way to make this happen is through marriage. In carrying out a marriage, sometimes unwanted things occur, to overcome them, one can do this, namely by submitting an application for annulment of the marriage to the court. Therefore, this issue is raised to answer the main issues, 1) What are the legal consequences for the cancellation of marriages due to illegal marriage guardians according to the laws and regulations in Indonesia? 2) Does the content of the judge's legal considerations in the Decision of the Central Jakarta Religious Court Number 193/Pdt.G/2019/Pa.JP comply with the laws and regulations in Indonesia? So this research was conducted normatively. The nature of the analytical descriptive research. How to draw conclusions with deductive logic. With data management, namely qualitative. The results of this study with reference to Article 28 of Law no. 1 of 1974 concerning Marriage jo. Article 75 Compilation of Islamic Law.